Occupational injuries and their sociodemographic, workplace, and behavioral determinants among large-scale factory workers in Ethiopia: a cross-sectional study - Ana Oña; Robel Tadele Forsido; Olena Bychkovska; Andrea Aegerter; Germán Guerra; Yacob Alemu Bizuneh; Kirubel Manyazewal Mussie (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Workplace injuries constitute a serious and growing public health concern worldwide. Despite work-related injuries being highly common, especially among workers in the manufacturing industry, their growing complexities are not adequately addressed in the current literature. Therefore this study aims to investigate the association between sociodemographic, workplace, and behavioral characteristics with work-related injuries among large-scale factory workers in Ethiopia. A cross-sectional study was conducted from February to April 2020 with 457 workers selected from large-scale factories in Addis Ababa, the capital of Ethiopia. Survey data included sociodemographic characteristics, working and safety conditions, and behavioral factors as predictors of occupational injuries. A logistic regression model was fitted to estimate the probability of injury and identify its associated factors. The 12-month prevalence of work-related injuries was 25%. Most injuries occurred at midnight (8.8%). Factors associated with work-related injury were excessive working hours (OR = 3.26; 95%CI: 1.26-8.41), cigarette smoking (OR = 2.72; 95%CI: 1.22-6.08), and manual handling (OR = 2.30; 95%CI: 1.13-4.72). Use of personal protective equipment reduced the odds of injury (OR = 0.42; 95%CI: 0.21-0.83). Although our estimated prevalence of occupational injury was lower than that found in other studies, our findings suggest that actions on modifiable conditions must be taken to reduce the burden of workplace injuries in Ethiopia. The results could inform preparedness and policy efforts aimed at improving worker safety and health.